Long Non-coding RNA EBLN3P Regulates UHMK1 Expression by Sponging miR-323a-3p and Promotes Colorectal Cancer Progression - Xu, Xiang-hao; Song, Wen; Li, Jun-hua; Huang, Ze-qi; Liu, Ya-fang; Bao, Qiang; Shen, Zhi-wen (Frontiers in Medicine, 2021)
Abstract Background: Growing studies have demonstrated that long non-coding RNA can act as crucial roles during the progression of various tumors, including colorectal carcinoma(CRC). We aimed to determine lncRNA endogenous bornavirus-like nucleoprotein (EBLN3P) expression in colorectal cancer (CRC) and examine its influence on tumor behaviors of CRC cells. Materials and methods: qRT-PCR was used to determine the expression levels of EBLN3P and miR-323a-3p in CRC tissues and cell lines. Cell viability, migration, invasion and apoptosis were assessed by CCK-8, colony formation, transwell assay and flow cytometry. Bioinformatics and dual-luciferase assays were used to investigate the interaction between EBLN3P and miR-323a-3p, as well as between miR-323a-3p and U2AF homology motif kinase 1 (UHMK1). Western blot was applied for detecting the expressions of the related proteins. Results: EBLN3P was highly expressed in CRC, and its high expression was distinctly associated with increased tumor size, histology/differentiation and advanced TNM stage and poor clinical outcome of CRC patients. EBLN3P silencing significantly inhibited the proliferation and metastasis, and induced the apoptosis of CRC cells. Furthermore, EBLN3P competed with endogenous RNA and enhanced the expression of UHMK1 by interfering with miR-323a-3p. Che correlation analysis confirmed the positive or negative association among EBLN3P, miR-323a-3p and UHMK1 Conclusion: EBLN3P promoted the development of CRC via targeting miR-323a-3p/UHMK1, which provided a new idea for treating CRC.